Values in peace psychology: The example of empirical research on Holocaust remembrance - Ruth Ditlmann; Berenike Firestone (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2025)
How do Holocaust remembrance projects affect participants? This is the topic of our research. We mainly conduct quantitative, empirical studies and use this method to understand the causal impact of projects. In doing so, we are often confronted with questions of normativity and come up against the limits of the ideal of objective (as in, value-free) research. This poses a particular challenge for empirical peace psychologists. However, normative judgments must be made transparent and discussed openly. It is obvious: our research on the impact of Holocaust remembrance projects is valuedriven. But isn't that a contradiction to the ideal of objective research? Values influenced, for example, our choice of research topic, the selection of dependent variables, and the interpretation of the results. These decisions are often difficult and require intensive engagement with normative judgments and a commitment to one's own values. It becomes clear that this entails a responsibility that, in our opinion, goes beyond that of a private individual. It also becomes clear that, given our topic, it is virtually impossible to conduct good empirical research without dealing intensively with normative questions. That is why we want our contribution to motivate other peace psychologists to make their normative decisions transparent and discuss them openly. First, of course, the question arises as to why one should even conduct empirical research on a topic that is so value-based. What can peace psychology contribute here? What can a quantitative empirical study on this topic look like?
Keywords: 320